Dopamine Supersensitivity: A Novel Hypothesis of Opioid-Induced Neurobiological Mechanisms Underlying Opioid-Stimulant Co-use and Opioid Relapse - Strickland, Justin C.; Gipson, Cassandra D.; Dunn, Kelly E. (Frontiers in Psychiatry, 2022)
Emergent harms presented by the co-use of opioids and methamphetamine highlight the broader public health challenge of preventing and treating opioid and stimulant co-use. Development of effective therapeutics requires an understanding of the physiological mechanisms that may be driving co-use patterns, specifically the underlying neurobiology of co-use and how they may facilitate (or be leveraged to prevent) continued use patterns. This narrative review summarizes largely preclinical data that demonstrate clinically-meaningful relationships between the dopamine and opioid systems with direct implications for opioid and stimulant co-use. Synthesized conclusions of this body of research include evidence that changes in the dopamine system occur only once physical dependence to opioids develops, that the chronicity of opioid exposure is associated with the severity of changes, and that withdrawal leaves the organism in a state of substantive dopamine deficit that persists long after the somatic or observed signs of opioid withdrawal appear to have resolved. Evidence also suggests that dopamine supersensitivity develops soon after opioid abstinence and results in increased response to dopamine agonists that increases in magnitude as the abstinence period continues and is evident several weeks into protracted withdrawal. Mechanistically, this supersensitivity appears to be mediated by changes in the sensitivity, not quantity, of dopamine D2 receptors. Here we propose a neural circuit mechanism unique to withdrawal from opioid use with implications for increased stimulant sensitivity in previously stimulant-naïve or inexperienced populations. These hypothesized effects collectively delineate a mechanism by which stimulants would be uniquely reinforcing to persons with opioid physical dependence, would contribute to the acute opioid withdrawal syndrome, and could manifest subjectively as craving and/or motivation to use that could prompt opioid relapse during acute and protracted withdrawal. Preclinical research is needed to directly test these hypothesized mechanisms. Human laboratory and clinical trial research is needed to explore these clinical predictions and to advance the goal of developing treatments for opioid-stimulant co-use and/or opioid relapse prevention and withdrawal remediation.